Pregnancy and epilepsy; meeting the challenges over the last 25 years: The rise of the pregnancy registries. (January 2017) - Kinney, M.O.; Craig, J.J.
Abstract: Purpose: Women with epilepsy (WWE), of all ages, have much to consider if their care is to be optimised and they are not to be denied the choices open to those without epilepsy. At no time is this more critical than during their child-bearing years when treatment decisions are complex. Methods: In this article we will provide a personal commentary and review of the pertinent literature on how the management of WWE of childbearing years has changed over the last 25 years. As well as reflecting on the state of knowledge at the start of the 1990s and the approach to managing WWE at this time, we will demonstrate that in addition to much more information now being available that there has also been an attempt to standardise how WWE should be managed. Results: As a means of achieving this increase in knowledge and standardisation of care, we argue that the various pregnancy registries have played a significant part in these positive developments. As vehicles for collecting clinically relevant data, they have provided information that has helped empower women and their health care providers to make sound clinical decisions, as well as highlighting the difficulties and unknowns. Conclusions: Still being active the pregnancy registries maintain a continued focus on the relevant issues relating to WWE.